Students’ pondering: An educational challenge to the arts and humanities in a market-oriented education system - Winther, Frederikke; Henriksen, Thomas Duus; Larsen, Gorm (Academic Quarter | Akademisk kvarter, 2016)
The purpose of this article is to address the educational aspect of pondering in terms of the reflection and reconsideration that the arts and humanities are both known and renowned for. While arts and humanities have, for many years, been under political pressure to adopt the more solution-oriented attitude of hard science, our students were quick to adopt this trend, too, and they are requesting classes and tools for quick-fixing, rather than activities that facilitate deep learning. Instead we argue for a two-sided approach, where critical reflection through pondering is in dialogue with and mutually supportive to problem-orientation. We discuss some perspectives and possibilities of learning that can enhance the reflective dimension of academic practice among students and report on an experiment that employs learning portfolios as a student-driven tool for facilitating the reflective pondering necessary for developing a professional identity that is focussed not only on solutions and presentations, but also on a deeper understanding of issues.